Emotional intelligence and academic performance: A predictive analysis of secondary school students in Edo State, Nigeria - Adubale, Andrew; Obioma, Emmanuela Odilamma (Journal of Advanced Guidance and Counseling, 2025)
Purpose – This study investigated the influence of emotional intelligence on the academic performance of senior secondary school students in Edo State, Nigeria. Method – A Descriptive survey research design was adopted, and 200 students constituted the sample for the study.   The emotional intelligence questionnaire (EIQ) was used to collect data for the study. The data was analyzed using regression analysis. Result – The findings showed that emotional intelligence significantly influenced the academic performance of the secondary school students. There was a significant difference in emotional intelligence by sex and age among students in their academic performance. Based on the study's findings, it was concluded that emotional intelligence has a significant influence on students’ academic performance. Implication – It was recommended that school counselors should provide skills acquisition training on emotional intelligence and also place an emphasis on strengthening emotional intelligence skills for both sexes. Originality/Value – This study contributes novel empirical evidence from the Nigerian educational context by demonstrating the significant predictive role of emotional intelligence on academic performance among secondary school students, while uniquely revealing gender and age-related variations that inform targeted counseling interventions for improving educational outcomes in West African learning environments. *** Tujuan – Penelitian ini bertujuan untuk menyelidiki pengaruh kecerdasan emosional terhadap prestasi akademik siswa sekolah menengah atas di Negara Bagian Edo, Nigeria. Metode – Desain penelitian survei deskriptif digunakan, dengan 200 siswa sebagai sampel penelitian. Kuesioner Kecerdasan Emosional (EIQ) digunakan untuk mengumpulkan data. Data dianalisis menggunakan analisis regresi. Hasil – Temuan menunjukkan bahwa kecerdasan emosional secara signifikan mempengaruhi prestasi akademik siswa sekolah menengah atas. Terdapat perbedaan yang signifikan dalam kecerdasan emosional berdasarkan jenis kelamin dan usia di antara siswa dalam prestasi akademik mereka. Berdasarkan temuan studi ini, disimpulkan bahwa kecerdasan emosional memiliki pengaruh yang signifikan terhadap prestasi akademik siswa. Implikasi – Disarankan agar konselor sekolah memberikan pelatihan pengembangan keterampilan kecerdasan emosional dan juga menekankan pada penguatan keterampilan kecerdasan emosional bagi kedua jenis kelamin. Orisinalitas/Nilai – Penelitian ini memberikan bukti empiris baru dari konteks pendidikan Nigeria dengan menunjukkan peran prediktif yang signifikan dari kecerdasan emosional terhadap prestasi akademik siswa sekolah menengah, sambil secara unik mengungkap variasi berdasarkan jenis kelamin dan usia yang dapat menjadi dasar intervensi konseling yang ditargetkan untuk meningkatkan hasil pendidikan di lingkungan belajar Afrika Barat.